Konstnärlig yttrandefrihet eller olaga hot i gangsterrap? En analys av den konstnärliga yttrandefrihetens gränser utifrån exemplet gangsterrap - Schüller,Gabriella (2025)
This analysis examines the right to freedom of artistic expression and its limits within Swedish law, using the example of unlawful threats in gangsta rap. This analysis also includes elements of a comparative method. By examining German law and judicial decisions, the aim is to place Swedish gangsta rap in a broader legal context. The analysis shows legal challenges related to gangsta rap – challenges that make it difficult to understand the boundaries between artistic freedom and criminal offenses such as unlawful threats. For a threat to constitute a criminal offense, it must be serious. Whether expressions in gangsta rap meet this threshold must be determined on a case-by-case basis, taking into account the cultural context. However, in the case of gangsta rap, assessing the cultural context is challenging due to the ambiguity between reality and fiction, as well as the distinction between the artistic persona and personal life. Moreover, the genre involves various forms of expression, not just lyrics, that can potentially be discussed as artistic or cultural expressions. The legal challenges related to gangsta rap risk leading to insecurity and unpredictability in legal assessments of when and how freedom of artistic expression should be protected and promoted, resulting in a lack of legal certainty. Ultimately, the analysis makes some remarks de sententia ferenda regarding the future assessment of the genre.
Keywords: Statsrätt; Straffrätt; Yttrandefrihet